Design and Analysis High Gain PHEMT LNA for Wireless Application at 5.8 GHz - Kamil Pongot; Abdul Rani Othman; Zahriladha Zakaria; Mohamad Kadim Suaidi; Abdul Hamid Hamidon; J.S. Hamidon; Azman Ahmad (Institute of Advanced Engineering and Science, 2015)
This research present a design of a higher gain (66.38dB) for PHEMT LNA using an inductive drain feedback technique for wireless application at 5.8GHz. The amplifier it is implemented using PHEMT FHX76LP transistor devices. The designed circuit is simulated with Ansoft Designer SV. The LNA was designed using T-network as a matching technique was used at the input and output terminal, inductive generation to the source and an inductive drain feedback. The low noise amplifier (LNA) using lumped-component provides a noise figure 0.64 dB and a gain (S21) of 68.94 dB. The output reflection (S22), input reflection (S11) and return loss (S12) are -17.37 dB, -15.77 dB and -88.39 dB respectively. The measurement shows the stability was at 4.54 and 3-dB bandwidth of 1.72 GHz. While, the low noise amplifier (LNA) using Murata manufactured component provides a noise figure 0.60 dB and a gain (S21) of 66.38 dB. The output reflection (S22), input reflection (S11) and return loss (S12) are -13.88 dB, -12.41 dB and -89.90 dB respectively. The measurement shows the stability was at 6.81 and 3-dB bandwidth of 1.70 GHz. The input sensitivity more than -80 dBm exceeded the standards required by IEEE 802.16.